The study of consumer purchase decision on medical and health insurance in Malacca / Fariz Syah Mohamed Ibrahim - Ibrahim, Fariz Syah Mohamed (Faculty of Business and Management, 2011)
There a lot of critical issue occurs in insurance industry and the awareness toward insurance product still become insolvent issue for centuries. Insurance have exist for decade and being used to transfer the risk that may become a burden to the insured (Shah M., 2008).There are numerous of product in insurance industry that relates to every single industry or individual who burden to the risk exposed in the environment. The type of insurance would be different according to the type of risk exposed to the individual and organization. Insurance services consist of life insurance and non–life insurance. In life insurance includes term insurance, whole life insurance, and annuity. Meanwhile, for non-life insurance includes motor insurance, fire insurance, and house owner insurance and other. This research paper will be focused on what makes insurance highly demand on medical and health insurance. The researcher already did a simple discussion with expertise related to the topic and trying to find the proximate cause that effect consumer purchasing decision to medical and health insurance. The study will try to determine the main factors that contribute to the buying behavior of medical and health insurance.